Contact Lenses for Color Blindness. Issue 12 (26th April 2018) - Badawy, Abdel‐Rahman; Hassan, Muhammad Umair; Elsherif, Mohamed; Ahmed, Zubair; Yetisen, Ali K.; Butt, Haider
Abstract: Color vision deficiency (color blindness) is an inherited genetic ocular disorder. While no cure for this disorder currently exists, several methods can be used to increase the color perception of those affected. One such method is the use of color filtering glasses which are based on Bragg filters. While these glasses are effective, they are high cost, bulky, and incompatible with other vision correction eyeglasses. In this work, a rhodamine derivative is incorporated in commercial contact lenses to filter out the specific wavelength bands (≈545–575 nm) to correct color vision blindness. The biocompatibility assessment of the dyed contact lenses in human corneal fibroblasts and human corneal epithelial cells shows no toxicity and cell viability remains at 99% after 72 h. This study demonstrates the potential of the dyed contact lenses in wavelength filtering and color vision deficiency management. Abstract : Color vision deficiency (color blindness) is an inherited genetic ocular disorder. A rhodamine derivative is incorporated in contact lenses to filter out the specific wavelength bands (545–575 nm) for application in color vision deficiency management. The biocompatibility of the contact lenses is assessed in human corneal fibroblasts and human corneal epithelial cells showing no toxicity and high cell viability.